اتجاهات بحوث الموهبة والتفكير في الوطن العربي = Talent and thinking research trends in the Arab world - Al-Hidabi, Dawood Abdulmalek Yahya; Muhammad Dib Al-Jaji, Reja (2016)
The research aimed to investigate the trends of talent and thinking research in the Arab world between 2006 - 2014 in selected conferences and academic journals. 188 research papers were selected for content analysis. The results showed: 1. Talented students’ identification research represents 66.5% whereas thinking and enrichment programs represent 33.5 % of all research papers. 2. Research dedicated for talented students were 49% whereas 22.3% for normal school students and university students were about 9%. 3. Quantitative research represents 96.8% of the research papers studied. 4. Descriptive research represents 70.7% while experimental and semiexperimental research represents 29.3% of research studied. 5. The use of questionnaire as a research tool represents 56.4% of research tools used whereas tests represent 35.6%. 6. 30% of the research population from secondary school students and other levels ranged from 0.5% to 14%. 7. 32% of the research conducting in Saudi Arabia, 16% in Jordan and 12.2% in Yemen, and 10% in the rest of the Arab countries.